Developing a core competency and capability framework for advanced practice physiotherapy: A qualitative study - Tawiah, Andrews K.; Stokes, Emma; Wieler, Marguerite; Desmeules, François; Finucane, Laura; Lewis, Jeremy; Warren, Jonathan; Lundon, Katie; Noblet, Tim; Cunningham, Caitriona; Woodhouse, Linda J. (Physiotherapy theory and practice, 2024)
There is an urgent need to develop an international competency and capability framework to support standardization of education and roles in advanced practice physiotherapy (APP). This need arose due to the rapid growth of the APP model of care, implemented out of necessity in the absence of agreement as to the competencies and capabilities or formal education required for the roles. This study explores the views and perceptions of practitioners and key stakeholders on a draft competency and capability framework for advanced practice physiotherapists. The purpose of this study was to: 1) gather feedback from key stakeholders (advanced practice physiotherapists, researchers, and leaders) on a draft competency and capability framework and 2) use that feedback to revise and improve the draft framework. Qualitative study using a series of four multi-national online focus groups. Thematic analysis was conducted according to Braun and Clarke. Sixteen participants from the United Kingdom, Ireland, Canada, Australia, and New Zealand participated in the study. Five themes were generated after data analysis: clinical expert, experienced communicator, strong leader, collaborator, and knowledge creator). A modified competency and capability framework was developed based on feedback from the focus groups and input from subject matter experts (SMEs). This study provides a modified core competency and capability framework comprising 24 competencies grouped under six domains. This study is a step toward international standardization of advanced practice physiotherapy based on a commonly agreed framework for the education and training of advanced practice physiotherapists.